Performance of Ultrasound in the Clinical Evaluation of Gout and Hyperuricemia. (5th April 2021) - Cao, Ling; Zhao, Tianyi; Xie, Chunmei; Zheng, Shucong; Wan, Weiguo; Zou, Hejian; Zhu, Xiaoxia
Abstract : Objective . To evaluate monosodium urate (MSU) crystal deposition and related lesions in the joints of patients with gout and hyperuricemia (HUA) using ultrasound. To explore the association between ultrasound findings and clinical features in gout and HUA. Methods . A total of 202 patients with gout and 43 asymptomatic patients with HUA were included. The clinical data and ultrasonic assessment results were collected and statistically analyzed. Results . Deposition of MSU crystals was found in 25.58% (11/43) of patients with asymptomatic HUA and 76.24% (154/202) of patients with gout. Of the 1, 082 joints from patients with gout examined, 33.09% (358/1082) displayed MSU crystal deposition. In the joints with MSU crystal deposition, 77.37% (277/358) had a history of attacks. Among the joints of gouty arthritis, double contour sign (DCS), hyperechoic aggregate (HAG), and tophi were found in 32.65% (159/487), 7.80% (38/487), and 24.64% (120/487) of the joints, respectively. DCS and tophi, but not HAG, increasingly appeared with the extension of gout duration. In patients with more than 15 years of gout history, DCS, Tophi, and HAG were found in 48.18%, 40.00%, and 6.36% of US assessed joints, respectively. In patients with gout, synovial lesion and bone erosion were found in 17.74% (192/1082) and 7.58% (82/1082) of joints, respectively. The synovial lesion was related to HAG, while bone erosion was related to tophi and DCS. Nephrolithiasis was detected in 20.30% (41/202) of patients with gout and 4.65% (2/43) of HUA patients, indicating that nephrolithiasis occurred in more patients with gout than in patients with HUA. Conclusion . HAG is an early performance of MSU crystal deposition in joints of gout and HUA. Both DCS and tophi are risk factors for bone erosion. Early urate-lowering therapy (ULT) should be considered in patients with gout, DCS, or tophi.